SEG Technical Program Expanded Abstracts 2012 2012
DOI: 10.1190/segam2012-0837.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional inversion of SQUID TEM data at Lalor Lake VMS deposit

Abstract: The combination of high fidelity and late time channels make SQUID magnetometers an attractive sensor for deep and highly conducting targets. Here we focus upon a data set acquired over the Lalor Lake VMS deposit. The deposit consists of a zinc zone between 700m and 1000m depth and a deeper gold/copper zone. The SQUID data set had previously been interpreted using the plate modeling to yield two conductors respectively corresponding to the zinc zone and the gold-copper zone. In this paper we invert these data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…We are also interested in the credibility of the deep extension of the conductor as revealed by the ground data inversion. Our previous work using inversion with hypothesis testing (Yang and Oldenburg, 2012) indicated that some conductive material at depth is required to fit the ground-based data.…”
Section: Alternative Model For Ground Datamentioning
confidence: 99%
“…We are also interested in the credibility of the deep extension of the conductor as revealed by the ground data inversion. Our previous work using inversion with hypothesis testing (Yang and Oldenburg, 2012) indicated that some conductive material at depth is required to fit the ground-based data.…”
Section: Alternative Model For Ground Datamentioning
confidence: 99%